2021
DOI: 10.5888/pcd18.200573
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Inadequate Sleep on Frequent Mental Distress

Abstract: What is already known on this topic? One-third of US adults report that they sleep less than the recommended amount, and approximately 20% have received a diagnosis of a mental illness. The link between inadequate sleep and mental distress has been viewed historically as a symptom-disease association with sleep inadequacies deriving from preexisting mental distress. What is added by this report?We examined the association between inadequate sleep and frequent mental distress in a diverse, population-based samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 16 publications
2
29
0
Order By: Relevance
“…This aligns with the association between sleep, physical activity, and diet during COVID-19 [ 28 - 30 ]. Furthermore, differences in SCN for Sleeping in groups with/without an Emotions challenge aligns with prior research on the impact of sleeping on overall mental health [ 31 , 32 ]. It is notable that more than half of the participants had challenges in the Emotions concept.…”
Section: Discussionsupporting
confidence: 78%
“…This aligns with the association between sleep, physical activity, and diet during COVID-19 [ 28 - 30 ]. Furthermore, differences in SCN for Sleeping in groups with/without an Emotions challenge aligns with prior research on the impact of sleeping on overall mental health [ 31 , 32 ]. It is notable that more than half of the participants had challenges in the Emotions concept.…”
Section: Discussionsupporting
confidence: 78%
“…Sleep and mental health are profoundly linked at a neurobiological level [ 2 ]. Both decreased sleep duration or quality can adversely impact mental health [ 3 , 4 ], and conversely, most mental health disorders present with objective or subjective alterations in sleep [ 2 , 5 ]. The causal relation between altered sleep and decreased mental health is evidenced by the fact that improvements in sleep translate to improvements in mental health such as depression, anxiety, rumination and stress [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, evidence from the 2018 Behavioral Risk Factor Surveillance System data including 273,695 U.S. adults aged 18-64 years found that participants with an average sleep duration ≤6 h nightly had 2.5 times (95% CI, 2.3-2.7) the odds of frequent mental distress compared with individuals who slept >6 h nightly. 20 Separately, adjusting for sleep duration, a study of 451,025 individuals using multiple Mendelian Randomization techniques found robust evidence supporting early diurnal preference as protective for depression and wellbeing. 21 Poor sleep quality, including sleep disorders and sleep disturbances, commonly co-occurs with mental health conditions.…”
Section: Introductionmentioning
confidence: 99%